2023
DOI: 10.1021/acsami.3c10945
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemical Engineering of a Metal 3D-Printed Flow Reactor Using a Metal–Organic Framework for Liquid-Phase Catalytic H2 Production from Hydrogen Storage Materials

Kohsuke Mori,
Tatsuya Fujita,
Hiroto Hata
et al.

Abstract: The accurate positioning of metal–organic frameworks (MOFs) on the surface of other materials has opened up new possibilities for the development of multifunctional devices. We propose here a postfunctionalization approach for three-dimensional (3D)-printed metallic catalytic flow reactors based on MOFs. The Cu-based reactors were immersed into an acid solution containing an organic linker for the synthesis of MOFs, where Cu2+ ions dissolved in situ were assembled to form MOF crystals on the surface of the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The CFD study indicated that a decrease in pore size from 2.0 mm to 1.5 mm caused a pressure drop (Δp) approximately 3 times greater, resulting in a negative effect on the catalytic activity by reducing the surface velocity. [15] Moreover, Li et al designed an optimum CuNi alloy monolithic catalyst for a reverse water-gas shift (RWGS) reaction combined with CFD method. Two different unit cell sizes of triply periodic minimal surface (TPMS) structure and honeycomb monolith were designed to investigate the effect of the geometric structure on the catalytic performance.…”
Section: Geometric Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The CFD study indicated that a decrease in pore size from 2.0 mm to 1.5 mm caused a pressure drop (Δp) approximately 3 times greater, resulting in a negative effect on the catalytic activity by reducing the surface velocity. [15] Moreover, Li et al designed an optimum CuNi alloy monolithic catalyst for a reverse water-gas shift (RWGS) reaction combined with CFD method. Two different unit cell sizes of triply periodic minimal surface (TPMS) structure and honeycomb monolith were designed to investigate the effect of the geometric structure on the catalytic performance.…”
Section: Geometric Structurementioning
confidence: 99%
“…recently proposed the utilization of metal organic frameworks (MOFs) as a modifier. The Cu‐based 3D‐printed reactors were immersed into an acid solution containing an organic linker for the synthesis of MOFs, where Cu 2+ ions dissolved in situ were assembled to form MOF crystals on the surface of the reactor [15] . This further allows carbonization, deposition of metal nanoparticles, and modification with organic molecules, enabling H 2 production from liquid‐phase hydrogen storage materials.…”
Section: Advancements In Metal 3d Printing Technology In Catalytic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Such spaces include environments that are surrounded by nanopore structures, as well as surface spaces that are strongly bounded from the surface. The design of such spaces involves the use of mesoporous materials [215][216][217][218], metal-organic frameworks (MOFs) [219][220][221][222], covalent organic frameworks (COFs) [223][224][225][226], self-assembled monolayers (SAM) [227][228][229][230], Langmuir-Blodgett (LB) film [231][232][233][234], layer-by-layer (LbL) assembly [235][236][237][238], etc.…”
Section: Introductionmentioning
confidence: 99%